Study of postures in sugarcane cutters in the Pontal of Paranapanema-SP, Brazil - Messias, Iracimara de Anchieta [UNESP]; Okuno, Emico (IOS Press, 2012)
The expansion of sugarcane monoculture in Brazil in the last decades has pointed out to the necessity of considering the question of sugarcane cutters occupational health. In this work we present a cross-sectional study aiming to examine the occupational posture of a group of sugarcane cutters, which work in a cane field located in the region of Pontal do Paranapanema-SP, Brazil. The study was made using the Ergonomic Analysis of Work - EAW methodology and the postural analysis method by Win-OWAS. Through the obtained records of postures, it was observed that during a workday the sugarcane cutters remain standing erect on two legs or in one leg 66% of the time and that their trunk remain tilted and in rotation, according to 63% of the positions categorized. It was also observed that the sugarcane cutter trunk performs repetitive and boundless movements during his routine of work, which can expose this individual to additional wear of their musculoskeletal functions. The activities in which the individual engages have favorable or adverse influence on his posture. The repetitive movements involved in specialized occupations are equivalent to repeated exercises, thus may be responsible for the excessive development of certain muscle groups. The study suggests that the postures adopted by sugarcane cutters can overload their musculoskeletal system and predispose the cutters to work-related musculoskeletal diseases.
Keywords: occupational health; sugarcane cutter; postures; win-owas; musculoskeletal disease